Approach to the history of communities in Ayacucho: The case of Quinua - Pereyra Chávez, Nelson Ernesto (2022)
This article analyzes the history of the peasant community of Quinua, in the department of Ayacucho. It seeks to identify those external and internal factors that led a group of indigenous settlers to form a collective that was recognized by the Peruvian State. Based on interpretation or hermeneutics and retrospective history, this paper postulates that the community appeared in the 16th century as a repartimiento and a reduction, but with characteristics and possessions different from the current ones, which were modified as the indigenous people claimed in trials the possession of royal lands. After modifying their propiety of the land and their power structure, the community achieved recognition by the State.